Oxidative stress and pesticide disease: a challenge for toxicology - Sandra Catalina Cortés-Iza (Revista de la Facultad de Medicina, 2018)
Introduction In the past decades, the synthesis of chemical compounds has resulted in a high number of substances used to protect crops from pests. Most pesticides have been used in large quantities for agricultural purposes. Acute and chronic poisoning are common among agricultural workers and the general population because of their use in different fields. Toxic exposure to these compounds is a major problem for toxicology, as it has an impact on public health due to its significant morbidity and disability. These compounds, when in contact with the human body, produce neurotoxic alterations and trigger molecular mechanisms related to lipid peroxidation, where reactive oxygen species can increase intracellular oxidative processes.Objective To carry out a review of the scientific literature related to diseases caused by oxidative stress induced by pesticides.Materials and methods A review of articles in PubMed was carried out using the keywords: Oxidative stress; Pesticides; Lipid peroxidation; Toxicity. The articles related to oxidative stress induced by pesticides were selected.Results Some hematological, neurological, metabolic and genotoxic diseases may be related to lipid peroxidation induced by pesticides.Conclusion This article presents a review of the scientific literature on oxidative stress, lipid peroxidation induced by pesticides and the different related diseases that can affect the general population.